The role of floating offshore wind in a renewable focused electricity system for Great Britain in 2050. (November 2018) - Moore, Andy; Price, James; Zeyringer, Marianne
Abstract: Floating offshore wind energy is an emerging technology that provides access to new wind generation sites allowing for a diversified wind supply in future low carbon electricity systems. We use a high spatial and temporal resolution power system optimisation model to explore the conditions that lead to the deployment of floating offshore wind and the effect this has on the rest of the electricity system for Great Britain in 2050. We perform a sensitivity analysis on three dimensions: total share of renewables, floating offshore costs and the impact of waves on operation. We find that all three impact the deployment of floating offshore wind energy. A clear competition between floating offshore wind and conventional offshore wind is demonstrated, with less impact on other renewable sources. It is shown that floating wind is used to provide access to greater spatial diversification. Further, access to more distant regions also affects the optimal placement of conventional offshore wind, as spatial diversification is spread between floating and bottom-mounted sites. Highlights: System and technology conditions impact the deployment of floating offshore wind. Floating offshore is used to provide access to greater spatial diversification. There is a clear competition between floating and conventional offshore wind. Floating offshore wind impacts the optimal placement of conventional offshore.